2021
DOI: 10.1029/2021jd035358
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Activation in Radiation Fog at the Atmospheric Radiation Program Southern Great Plains Site

Abstract: Supersaturation during eight radiation fog cases at a rural site in Oklahoma, USA is found to vary from 0.01% to 0.06% • Evidence of initial dry particle size distribution and aerosol hygroscopicity affects nucleation scavenging efficiency • The lowest dry activation diameter during each fog event was typically between 300-400 nm and wet activation diameters ranged from 2 to 7 µm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
(173 reference statements)
1
3
0
Order By: Relevance
“…The evolutions of estimated supersaturations during the fog episode on 11‐04 are also shown in Figure 2b, indicating that supersaturation reached a peak of approximately 0.034% after about 2 hr of fog initiation, remained steady for approximately 1 hr, and then gradually decreased until fog dissipation. The estimated peak supersaturation of 0.034% is in line with values reported in Europe (Boutle et al., 2018; Hammer et al., 2014; Mazoyer et al., 2019), China (Shen et al., 2018), and North America (Wainwright et al., 2021), further confirming the low supersaturation characteristics of fogs globally.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The evolutions of estimated supersaturations during the fog episode on 11‐04 are also shown in Figure 2b, indicating that supersaturation reached a peak of approximately 0.034% after about 2 hr of fog initiation, remained steady for approximately 1 hr, and then gradually decreased until fog dissipation. The estimated peak supersaturation of 0.034% is in line with values reported in Europe (Boutle et al., 2018; Hammer et al., 2014; Mazoyer et al., 2019), China (Shen et al., 2018), and North America (Wainwright et al., 2021), further confirming the low supersaturation characteristics of fogs globally.…”
Section: Resultssupporting
confidence: 84%
“…Lower supersaturation values correspond to larger critical activation diameters. Previous research on fog activation has revealed the typically low supersaturation conditions of fogs, often below 0.1% (Boutle et al., 2018; Shen et al., 2018; Wainwright et al., 2021). This low supersaturation environment makes it challenging to clearly differentiate between activated and non‐activated aerosols.…”
Section: Field Measurements and Methodsmentioning
confidence: 99%
“…Considering the shattered particles and interstitial aerosols (i.e., unactivated particles), fog droplets were identified to be greater than 2 μm in diameter, and fog with N f ${\ge} $ 10 cm −3 and LWC ${\ge} $ 1 mg m −3 was identified (Lu et al., 2020; Wang, Niu, et al., 2021), which is the same as the criterion of cloud identification (e.g., Deng et al., 2009; Yang et al., 2019; Zhao et al., 2019). It should be noted that interstitial aerosols could still be present in the FDSD, particularly in the small droplet size (Shen et al., 2018; Mazoyer et al., 2019; Wainwright et al., 2021). As shown in Table 1, eight fog cases with 88,962 FDSDs were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Thereto, CCN could activate into fog droplets, leading to an increase in N, especially for the small droplets. It should be noted that the interstitial aerosols could contribute significantly to N (Shen et al, 2018;Mazoyer et al, 2019;Wainwright et al, 2021), because of the generally low supersaturation in fogs and relatively high aerosol loading in this region. After 5:15 a.m. (beginning of the mature phase), the continuous activation (Devenish et al, 2012) and condensation processes caused a significant fog droplets number concentration at each stage.…”
Section: Fog Scavenging Effectsmentioning
confidence: 99%